Fenomenologi Transendental Dalam Transparansi dan Akuntabilitas Performance Based Budgeting - Yanuarisa, Yesika; Irianto, Gugus; Rosidi (Universitas Brawijaya, Indonesia, 2014)
This study aims to understand the meaning of transparency and accountability of performancebased budgeting Central Kalimantan provincial government. This study is a qualitative research approach used transcendental phenomenology to uncover the basic meaning of transparency and accountability. The results showed that the meaning of transparency in the performance -based budget includes openness of the budget process by the Central Kalimantan provincial government involving the community with the budget as a policy delivery obligations with willingness is supported by the accessibility of the budget document as an act of open road leads to the documents necessary for the public budget. Central Kalimantan provincial government mandated budget to account for the public in the form of Budget Responsibility Reports Revenue and Expenditure. Accountability interpreted performance based budgeting of the main tasks and functions that constitute performance information in planning performance as the basis for allocation of performance-based budgeting for aid accountability budget contained in the Accountability Document Implementation budget. Evaluation of performance as a result of performance feedback on current and past as a basis and lessons to improve future performance. Performance Accountability Report Preparation Government Agencies as one of the obligations of local government agencies that still need improvement.